2016
DOI: 10.1186/s12889-016-3450-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized evaluation and cost-effectiveness of HIV and sexual and reproductive health service referral and linkage models in Zambia

Abstract: BackgroundProvision of HIV prevention and sexual and reproductive health services in Zambia is largely characterized by discrete service provision with weak client referral and linkage. The literature reveals gaps in the continuity of care for HIV and sexual and reproductive health. This study assessed whether improved service delivery models increased the uptake and cost-effectiveness of HIV and sexual and reproductive health services.MethodsAdult clients 18+ years of age accessing family planning (females), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 29 publications
(23 reference statements)
0
60
0
Order By: Relevance
“…The systematic search returned 3704 unique entries, after duplicates were removed. Screening and application of eligibility criteria produced 19 studies for inclusion in the review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Figure 2 shows the results of the study selection process.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic search returned 3704 unique entries, after duplicates were removed. Screening and application of eligibility criteria produced 19 studies for inclusion in the review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Figure 2 shows the results of the study selection process.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Pap smear or cytology-based cervical screening was assessed most often (n = 6, 31.6%) [16,17,21,26,31,33]. A quarter of studies (n = 5, 26.3%) did not specify which screening test was being performed [20,22,24,29,32]. Multiple screening methods were used in some studies, such as those that compared uptake of HPV self-sampling to facility-based visual inspection screening methods [19,25,27,28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Integrating cervical cancer services into existing HIV and family planning programs promotes increased efficiencies through use of common health personnel and infrastructure, compared with vertical SRH programming . Significant global investments have been made to increase provision of HIV testing, treatment, and care, and these investments can be maximized by adding cervical cancer prevention services .…”
Section: Benefits Of Integrated Srh Servicesmentioning
confidence: 99%
“…IntegratingcervicalcancerservicesintoexistingHIVandfamilyplanning programs promotes increased efficiencies through use of commonhealthpersonnelandinfrastructure,comparedwithverticalSRH programming. 11,12,16 Significant global investments have been made to increase provision of HIV testing, treatment, and care, and these investments can be maximized by adding cervical cancer prevention services. 4,12,16 In 2015, the Global Fund for AIDS, Tuberculosis andMalariaannouncedthatitwillallowcountriestoincludecervical cancerservicesintheirGlobalFundrequests, 27 openingthedoorto increasedfundingfortheseservices.…”
Section: Efficient and Cost-effective Use Of Resources And Infrastrmentioning
confidence: 99%
“…Clinics could improve efficiency by reducing registration wait time through integration of cervical cancer screening as part of a larger package of maternal services; for example, integrating with HIV testing and care. One study in Zambia found that increasing linkages and improving integration of HIV and sexual and reproductive health services led to more cost-effective service delivery [31]. …”
Section: Discussionmentioning
confidence: 99%